ANALISIS PENYALAHGUNAAN GADGET PADA REMAJA SEKOLAH MENENGAH ATAS (SMA) DI KOTA PALEMBANG - Rina Agustina; Khadijah Lubis (Inteligensi : Jurnal Ilmu Pendidikan, 2025)
Technology makes life easier with various features that can help humans in various daily activities. One of the technologies used by humans in this digital era is gadgets. Gadgets are considered superior compared to other electronic devices, as they have different functions and characteristics. Apart from providing benefits for individuals in their daily lives, it turns out that gadgets have the potential to be misused. One of them is in the use of entertainment media, such as online games. This study aims to determine the description of the level of gadget abuse based on the use of online games in adolescents at SMA Negeri 10 Palembang. This research uses quantitative descriptive method. The sampling technique in this study used Simple Random Sampling. The sample of this study consisted of X and XI classes totaling 327 students. The instrument in this study used a gadget abuse scale developed by researchers having a validity of 0.05 and a reliability of 0.867. The results showed that gadget abuse based on students' online games was in the moderate category with a Mean of 98.85, which amounted to 250 students (76%) in the moderate category.